The Behavioral Investigation of Industry 4.0 Concept: A Research On Twitter - Bulent Cekic (The Central European Review of Economics and Management (CEREM), 2020)
Aim: This paper is going to investigate how Industry 4.0 concept especially the components of it, behaves in social networks and the context of this innovative approach find a place in time in means of content and sentiment comprising. Design / Research methods: Expeditious progress in industrialization and information techniques has made great advancement in developing the next span of production technology. Industry 4.0 is an imperative action where the intention is the alteration of modern production through digitalization and profiteering of the capabilities of new advancements. Today, the absence of powerful appliances still feigns a significant impediment for utilizing the ample potential of Industry 4.0. Notably, behavioral approaches are essential for understanding Industry 4.0, which professes novel trials. This paper briefly surveys the area of Industry 4.0 as it relates to behavioral operations by using sentiment analysis and social network analysis methods and tools by describing features of the relationship network either through numerical and visual representation Conclusions / findings: First of all, it should be presumed that the name Industry 4.0 describes various, fundamentally internet-based developments in manufacturing operations. These advancements do not only have technological but moreover accomplished organizational engagements. Appropriately, a shift from product to service orientation is assumed. Following, the introduction of novel varieties of businesses can be envisioned which embraces new particular functions within the production process sequentially the value-creation networks. Originality / value of the article: Within the context of the current state of the art in operations management literature, this paper fulfills the gap between behavioral operations and industry 4.0 context for the researchers both in operations management and behavioral sciences will benefit from this analysis.
Keywords: C88; D23; D24; E71; M11; O14; O33; 330; Behavioral Operations Management; Sentiment Analysis; Industry 4.0; Social Network Analysis